Probiotic Lactobacillus rhamnosus GG Induces Alterations in Ileal Microbiota With Associated CD3-CD19-T-bet+IFNγ+/- Cell Subset Homeostasis in Pigs Challenged With Salmonella enterica Serovar 4,[5],12:i:- - Zhang, Wei; Wu, Qiong; Zhu, Yaohong; Yang, Guiyan; Yu, Jiao; Wang, Jiufeng; Ji, Haifeng (Frontiers in Microbiology, 2019)
Salmonella enterica serovar 4,[5],12:i:- (S. 4,[5],12:i:-) is an emerging foodborne pathogen causing salmonellosis in humans and animals. Probiotic Lactobacillus rhamnosus GG (LGG) is an effective strategy for controlling enteric infections through maintaining gut microbiota homeostasis and regulating the intestinal innate immune response. Here, LGG was orally administrated to newly weaned piglets for 1 week before S. 4,[5],12:i:- challenge. S. 4,[5],12:i:- challenge led to disturbed gut microbiota, characterized by increased levels of Psychrobacter, Chryseobacterium indoltheticum, and uncultured Corynebacteriaceae populations, as well as an aberrant correlation network in Prevotellaceae NK3B31 group-centric species. The beneficial effect of LGG correlated with attenuating the expansion of Prevotellaceae NK3B31 group. Fusobacterium only found in the pigs treated with LGG was positively correlated with Lactobacillus animalis and Propionibacterium. Administration of LGG induced the expansion of CD3-CD19-T-bet+IFNγ+ and CD3-CD19-T-bet+IFNγ- cell subsets in the peripheral blood at 24 h after a challenge of S. 4,[5],12:i:-. S. 4,[5],12:i:- infection increased the population of intraepithelial CD3-CD19-T-bet+IFNγ+ and CD3-CD19-T-bet+IFNγ- cells in the ileum; however, this increase was attenuated via LGG administration. Correlation analysis revealed that LGG enriched Flavobacterium frigidarium and Facklamia populations, which were negatively correlated with intraepithelial CD3-CD19-T-bet+IFNγ+ and CD3-CD19-T-bet+IFNγ- cells in the ileum. The present data suggest that probiotic LGG alters gut microbiota with associated CD3-CD19-T-bet+IFNγ+/- cell subset homeostasis in pigs challenged with S. enterica 4,[5],12:i:-. LGG may be used in potential gut microbiota-targeted therapy regimens to regulate the specific immune cell function and, consequently, control enteric infections.